Robust production of sustainable concrete through the use of admixtures and in-transit concrete management systems. (August 2019) - Berodier, Elise; Gibson, Larry R.; Burns, Elizabeth; Roberts, Lawrence; Cheung, Josephine
Abstract: The production of sustainable building materials, such as concrete, has drawn more and more attention in the last decade. Breakthroughs in the development of new admixtures, new mix designs, new concrete management systems, together with deeper understanding on the best-mode usage of admixtures with different cementitious materials have resulted in production of sustainable concrete with better performance at a lower cost. This paper reviews the latest mechanistic understanding on how admixtures interact with cement and cementitious materials, real-world examples on current practical challenges faced by concrete producers, and an example on the advances allowed by the use of transformational technologies for improved concrete management systems. We also highlight new technical challenges and conditions to investigate these gaps in hope to better coordinate research efforts critical to the industry.